PERAN NOTARIS DALAM MEMBERIKAN KEPASTIAN HUKUM PADA KANTOR NOTARIS MOH DJAELANI ASâAD DI KABUPATEN SLEMAN (Pasca Lahirnya Undang Undang Nomor 30 Tahun 2004) - , MUHAMMAD WILDAN NAFI' ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Article 62 letter b of law no. 30 year 2004 concerning notary mention that the handover protocol can be implemented in terms of a notary term has expired . Implementation of the protocol submission further described in article 63 paragraph (1) and article 63 paragraph (4) of the law that is submitted later than 30 days and given to another notary appointed by the Council of Ministers upon the recommendation of the Regional Supervisor . This study aims to determine the role of the notary in providing legal certainty to the certificate stored in the office as part of evidence in judicial proceedings, and to know the notary business storage protocols over the deed that had been kept prior to his appointment as a notary public administrative receiver protocol is completed. This study is an empirical study is to see, examine how the working of the law in society. This study focuses on the research field (field research) to obtain primary data obtained from interviews with informants. The research is fitted with a research library (library research) to obtain secondary data by looking for theories, views were strongly correlated and relevant to the issues to be studied. Based on the results it could be concluded that the notary does not have a role in providing legal certainty to the certificates that are stored in the office as part of evidence in judicial proceedings. Notary only have a moral responsibility to preserve and store the protocol in the state archives office that is not broken and confidentiality is assured. Notary is not entitled to issue a protocol to the appointment as a notary public administrative receiver completed the protocol. Act has not expressly provide closure for the delay time caused by handover protocol recommendation for the appointment as a notary protocol receiver of Ministers has not been fully processed.